DEVELOPMENT OF INFORMATION SYSTEMS THAT PROVIDE STRATEGIC CHOICE (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The dynamic market environment causes constant updating and increasing the amount of information, which isespecially important for the process of strategic choice of the enterprise. This requires the use of information systemsthat support strategic choice.The purpose of the article is to consider the dynamics of approaches to strategic management and their provisionof information systems, and to explore the features of modern aspects of the use of information systems andtechnologies of enterprises to improve the effectiveness of strategic choice.It is substantiated that the implementation of information systems is associated with the complexity ofconfiguration, configuration and updating, the complexity of their implementation, often forced to change the way offunctioning through technical, IT, cultural, restructuring and organizational aspects, as well as business features.Knowledge is important. as on the part of the enterprise where the systems are installed, software vendors,implementation teams and related services of implementation methods related to specific systems.Based on the analysis of scientific achievements of world and Ukrainian scientists of information managementsystems, the classification of information systems that support strategic choice in the enterprise is proposed. Theproposed division takes into account the nature of the strategic selection process and the possible amount ofinformation support for management information systems and can be used by enterprises to determine opportunities forfuture development.It is established that the changes taking place in the perception of strategic orientation of enterprises and ITsystems for management needs.It is proved that the assessment of information technology prospects allows to form a correct real assessment ofnew capabilities of the organization in order to increase its competitiveness through the introduction of informationtechnology, consider ways to change relations with consumers, suppliers, develop strategies for implementing specificinformation technologies. in general, justify the necessary measures to maintain a given level of reliability in specificareas of activity in the use of information technology, develop their own plan for the implementation of the requiredinformation technology, taking into account the reaction of the environment and, in particular, competitors.
Keywords: strategic choice, classification of information systems, Transaction Processing Systems, Management Information Systems, Knowledge Management Systems, Executive Support Systems.